Adsorption of hydrogen sulfide on synthetic and carbon adsorbents: Isotherms and mechanism - Ergashev, Oybek; Bakhronov, Khayot; Kokhkharov, Mirzokhid; Zebo, Jumaboeva; Bazarbaev, Muratali; Sultonov, Amirkhon; Sobirjonova, Surayyo; Juraeva, Ziyoda; Asfandiyorov, Marufjon; Gaybullayeva, Dildora (Edelweiss Applied Science and Technology, 2025)
The adsorption of hydrogen sulfide (H2S) was studied using the adsorption calorimetric method at a constant temperature of 303 K. The objects of study were CaA-type zeolites with different cationic compositions and a carbon adsorbent obtained by microwave activation of Paulownia tomentosa bark. The obtained adsorption isotherms were processed using the Dubinin–Radushkevich equation, which made it possible to determine the adsorption capacity, characteristic energy, and the nature of the interaction between H2S molecules and the active surface sites. The isotherm expressed in the three-term form of the Volume Micropore Occupation Theory (VMOT) equation showed complete agreement with the experimental data. Based on these equations, the adsorption isotherm was calculated up to the saturation vapor pressure of H2S. Calorimetric results indicated a moderate exothermic effect typical of predominantly physical adsorption accompanied by weak chemisorption on certain active centers. Differences in the sorption behavior of zeolites and the carbon adsorbent were attributed to variations in pore structure, surface polarity, and the concentration of active sites. The obtained results refine the thermodynamic characteristics of the H2S-solid adsorbent system and can be applied to the development of efficient technologies for the purification of natural and industrial gases from hydrogen sulfide.